Protective Effects of Bitter Almond Kernel Extract on Liver and Kidney Tissues in Streptozotocin-Induced Diabetic Rats - Demır, E.; Keser, S.; Yılmaz, Ö. (Fırat University, 2015)
The bitter almond has been used for a long time by diabetes patients due to some important anti-diabetic effects. In this study, we aimed to determine protective effects of bitter almond extract on the lipid-soluble vitamins, cholesterol, glutathione (GSH), total protein, malondialdehyde (MDA), fatty acid levels of liver and kidney tissues of streptozotocin-induced diabetic rats. According to our findings, in kidney tissue, GSH and total protein were decreased in the Diabetes (D) and Diabetes + Bitter Almond (D+A) groups. Again MDA was increased in the D group, but not changed in the D+A group. Our results indicated that bitter almond extract might have a positively effect on postprandial blood glucose levels, as well as, on the GSH and MDA levels in the kidney tissue. The decrease of postprandial glucose level and these positive results can be attributed to bitter almond extract in the kidney tissue. The bitter almond and streptozotocin (STZ) administrations affected amount of some important fatty acids in the liver and kidney tissues, which substrates in fatty acid metabolism on duty enzymes.

Acı badem bazı önemli anti-diyabetik etkileri nedeniyle diyabet hastaları tarafından uzun bir süredir kullanılmaktadır. Bu çalışmada acı badem ekstresinin streptozotosin kaynaklı diyabetik sıçanların karaciğer ve böbrek dokularında yağda çözünen vitaminler, kolesterol, glutatyon (GSH), total protein, malondialdehit (MDA) ve yağ asitleri seviyeleri üzerinde koruyucu etkilerini saptamayı amaçladık. Bulgularımıza göre böbrek dokusunda, GSH ve total protein miktarı Diyabet (D) ve Diyabet + Acı Badem (D+A) gruplarında azalmıştır. Yine MDA seviyesi D grubunda artmış, D+A grubunda ise değişmemiştir. Sonuçlarımız göstermiştir ki acı badem ekstresi postprandial kan glukoz seviyesi yanında böbrek dokusunda GSH ve MDA seviyeleri üzerinde pozitif etkilere sahip olabilir. Postprandial kan glukoz seviyesindeki azalma ve böbrek dokusundaki bu pozitif etkiler acı badem ekstresine atfedilebilir. Ayrıca acı badem ve streptozotosin uygulamaları karaciğer ve böbrek dokularında yağ asidi metabolizmasında görevli enzimlerin substratı olan bazı önemli yağ asitlerinin miktarını etkilemiştir.
Streptozotosin-Kaynaklı Diyabetik Sıçanların Karaciğer ve Böbrek Dokularında Acı Badem Çekirdek Ekstresinin Koruyucu Etkileri